Pls answer my question
1)find the quadratic polynomial with zeroes 3+√2 & 3-√2.
2)if alpha*beta are zeroes of x^2 +7x+12,then find the value of (1/2)alpha +(1/2)beta-2(alpha*beta).
3)if alpha ,beta are the ratio of quadratic polynomial p(x)=x^2-(k-6)x+2(2k-1). find the value of k ,if alpha +beta =(1/2alpha*beta).

2
Pls answer fast!!!!!

Answers

2015-04-26T19:33:58+05:30
Let 3+root2 = alpha      and      3 - root 2 = beta
then
alpha + beta = ( 3 + root 2 ) + ( 3 - root 2 )
                  =  3 + root 2 + 3 - root 2
                   [ + root 2 and - root 2 gets cancelled ]
                   = 3 + 3
                   = 6
alpha * beta = ( 3 + root 2) ( 3 - root 2 )
                  = 3( 3 - root 2 ) + root 2 ( 3 - root 2 )
                  = 9 - 3 root 2 + 3 root 2 - 2
                  [ -3 root 2 and + 3 root 2 gets cancelled ]
                  = 9 - 2
                  = 7

rule : -          x square + ( alpha + beta ) x - (alpha*beta)
              
                 = x square + 6 x - 7         is the required polynomial
1 2 1
completed
I Mean 2&3
oh those got 2 check it . ill try those
OK!
Pls do fast!
The Brainliest Answer!
2015-04-27T00:44:34+05:30

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
1) sum of roots = 3 + √2 + 3 - √2 = 6
    product of roots = (3+√2) (3-√2) = 3² - 2 = 7
    quadratic polynomial =  x² - sum of roots + product of roots
                       x² - 6 x + 7 

2)   α + β = - coefficient of x / coefficient of x² = -7
       α β = constant term / coefficient of x² = 12
                 1/2 α + 1/2 β - 2(α β) = 1/2 (α + β) - 2 αβ = -7/2 - 2 * 12 = -55/2

3)  x² - (k-6) x + 2 (2k-1) 
         α + β = k  - 6
           α β = 4 k - 2
  
     as α + β = 1/ (2αβ) ,         k - 6 = 1/(8 k -4)
                  
           8 k² - 4 k - 48 k + 24 = 1
          8 k² - 52 k  + 23 = 0
               factors of  23 * 8 =  23 * 2 * 6 =  46 * 6 whose sum is 52.
            8k² - 4 k - 46 k + 23 = 0
            4 k (2 k - 1) - 23 (2k - 1) = 0
                  (4k - 23) ( 2k - 1) = 0

      k = 1/2 or  23/4

2 5 2
please click onthe thanks button blue.. above...
Tanx!
U helped a lot!!